Innovation of Active and Attractive Learning Models to Increase the Effectiveness of Islamic Religious Education: (Inovasi Model Pembelajaran Aktif dan Atraktif dalam Meningkatkan Efektivitas Pendidikan Agama Islam) - Simanullang, Malik Akbar; Abuddin Nata; Siti Khadijah (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2026)
Abstract: This study aims to analyze the innovation of active and attractive learning models in increasing the effectiveness of Islamic Religious Education (PAI). In implementing this learning model, teachers and students must play an active role in the learning process, especially educators as learning facilitators. And the method used in this study is qualitative with the type of library research (literature study), where researchers searched for various journal articles, books, and other scientific works that are relevant to the research study as references in writing. The results of the study show that by implementing active and attractive methods in Islamic Religious Education (PAI) learning, an effective learning will be created which will make students more active not only listening, but they can be more optimal in learning. So in this case, teachers as educational facilitators must have what is called a teacher's competence that will lead students to achieve learning goals. The purpose of this study is to see how active and attractive learning methods can be more effective in learning, so that students and teachers are easier to achieve learning goals.